6-Gingerol inhibits proliferation in gastric cancer via the STAT3 pathway in vitro - Li, Li; Ji, Yi; Ma, Yan-Xia; Gao, Liang-Qin; Zhou, Hong-Guang; Wu, Mian-Hua (Cellular and Molecular Biology, 2019)
The Editor-in-Chief has retracted this article. All authors agree to this retraction.